Respostas

A melhor resposta!
  • Usuário do Brainly
2014-08-22T00:49:03-03:00
Seja AD=h.

No triângulo ABD, temos que, \text{tg}~60^{\circ}=\dfrac{AB}{AD}.

Assim, \sqrt{3}=\dfrac{x}{h}~~\texttt{(i)}.

Além disso, no triângulo ABC, vemos que:

\text{tg}~30^{\circ}=\dfrac{AB}{AC}

Deste modo, \dfrac{\sqrt{3}}{3}=\dfrac{x}{20+h}~~\texttt{(i)}.

De \texttt{(i)}, tiramos que, h=\dfrac{x}{\sqrt{3}}=\dfrac{x\sqrt{3}}{3}.

De \texttt{(ii)}, temos (20+h)\sqrt{3}=3x, daí segue que, h=\dfrac{3x\sqrt{3}}{3}-20.

Logo:

\dfrac{x\sqrt{3}}{3}=\dfrac{3x\sqrt{3}}{3}-20

x\sqrt{3}=3x\sqrt{3}-60

3x\sqrt{3}-x\sqrt{3}=60

2x\sqrt{3}=60

x\sqrt{3}=30

Deste modo, x=\dfrac{30}{\sqrt{3}} e obtemos x=\dfrac{30\sqrt{3}}{3}

Portanto, x=10\sqrt{3}~\text{m}.
2 5 2